Клиническая оценка эффективности применения фотодинамической терапии в профилактике развития вторичного кариеса у детей региона Верхнего Потысья - Потапчук, Анатолій Мефодійович; Алмаші, Василь Миколайович (Actual Dentistry, 2020)
Асtuаl tу. Laser technologies are opening a new perspective in the treatment of caries and its complications. The antibacterial effect of the red diode laser in combination with its unique biostimulating properties can be used to selectively inhibit pathogenic microflora. Data on the use of PDT in the dental practice of protocols for the prevention of secondary carious lesions of the hard tissues of the teeth is extremely scarce. The relevance of studying the aspects of photodynamic is a real alternative to traditional methods of antibacterial exposure in the pathogenesis of caries. Aim. Evaluation of the effectiveness of photodynamic therapy in the prevention of the development of secondary dental caries. Materials and methods. The treatment of permanent dental caries was performed in 54 children of the Upper Tysa region aged 12–15 years. Using the method of laser-induced fluorescence and visual-instrumental techniques, we determined the clinical effectiveness of the use of photodynamic therapy in the prevention of the development of secondary dental caries. Results. The analysis of long-term clinical results showed that within 12 months after treatment of dentine caries in the control group of the study, where antiseptic treatment of carious cavity was carried out with 0.12 % solution of chlorhexidine, in 10.35 % of cases according to the criterion USPHS observed violations of marginal alignment, no secondary caries was detected in any of the study groups. According to the results of the study of patients in the control group after 18 months, it was found that in 17.25 % of cases violations of the marginal adaptation of the restorations were observed, of which in 6.9 % cases the presence of secondary caries was confirmed, which was confirmed by laser-induced fluorescence. Conclusions. Analysis of clinical data showed that 18 months after treatment, the best condition of composite restorations was observed in patients whose antiseptic treatment of carious cavities was carried out using photodynamic therapy with exposure time of 60 s treatment of dentine caries using traditional antiseptic treatment. Key words: secondary caries, children, USPHS criteria, laser-induced fluorescence, PDT (photodynamic therapy).